Post partum ovarian activity and uterine involution in the suckled swamp buffalo (Bubalus bubalis) - Jainudeen, Mohamed Razeen; Bongso, T. A.; Tan, H. S. (Elsevier, 1983)
Ovarian activity and uterine involution were monitored by rectal palpation, oestrus detection and plasma progesterone analysis from 3 to 4 days to approximately 150 days post partum in 38 suckled swamp buffaloes (Bubalus bubalis). The intervals from parturition to regression of the corpus luteum (CL) of pregnancy and involution of the uterus were 10 and 28 ± 6 (S.D.) days respectively. First detected oestrus and first elevation of plasma progesterone (> 0.7 ng/ml) occurred at 88 ± 26 and 96 ± 22 days in 8 and 12 buffaloes respectively. During the first 150 days post partum, 26 of 38 suckling buffaloes (68%) were acyclic (anoestrus) and of 12 animals (32%) exhibiting ovarian cycles, 4 were not detected in oestrus. The tentative diagnosis, based on rectal palpation, that CL were present between days 30 and 90 after parturition (without concurrent luteal levels of progesterone in plasma) suggests that confirmation should be by laparoscopy. It is concluded that a delay in the resumption of ovarian cyclicity post partum represents an important factor contributing to the prolonged calving to conception interval in the suckled swamp buffalo.